Protected engagement time on older adult mental health wards: A thematic analysis of the views of patients, carers, and staff. (21st April 2017) - Dodd, Emily; Cheston, Richard; Procter, Charlie; Heneker, Sarah; Gray, Richard; Fox, Chris; Nolan, Fiona
Abstract: During protected engagement time (PET), ward routines are adjusted so that staff can spend time together with patients without interruption. The aim of PET is to increase staff and patient interaction on wards, and ultimately patient well‐being. Although PET has been implemented on inpatient wards within the UK, including older adult wards, there is no systematic evidence as to how PET is carried out or how it is experienced by staff, patients, and families. Semistructured interviews were conducted with 28 participants (8 patients, 10 family members, and 10 ward staff) from three different wards with PET, and transcriptions were analysed using thematic analysis. Three themes were identified: (i) the patient is at the heart of care; (ii) PET depends on staff; and (iii) tensions in how PET operates. There was support in our sample for the principles of PET and its potential for a positive impact on patient well‐being. However, the implementation of PET was identified as challenging, highlighting an existing tension between an individual's needs and the wider needs of patients on the ward as a whole. The impact of PET was generally described as being dependent on how PET was organized and the level of staff commitment to PET. Participants emphasized that if PET is to be successful, then it should be a fluid process that fits in with the local context.